Growth and yield of okra as influenced by hill elevation and plant de-detoping in hill slope condition - Firoz, ZA; Nasiruddin, KM; Mondal, MF; Farooq, AM (Bangladesh Journal of Agricultural Research, 2010)
Keywords: Okra yield; plant growth; hill elevation; de-topping. DOI: 10.3329/bjar.v35i2.5898 Bangladesh J. Agril. Res. 35(2) : 355-358, June 2010